The Diverse Search for Synthetic, Semisynthetic and Natural Product Antibiotics From the 1940s and Up to 1960 Exemplified by a Small Pharmaceutical Player - Leisner, Jørgen J. (Frontiers in Microbiology, 2020)
The 1940s and 1950s witnessed a diverse search for not just natural product antibiotics but also for synthetic and semisynthetic compounds. This review revisits this epoch, using the research by a Danish pharmaceutical company, LEO Pharma, as an example. LEO adopted a strategy searching for synthetic antibiotics toward specific bacterial pathogens, in particular Mycobacterium tuberculosis, leading to the discovery of a new derivative of a known drug. Work on penicillin during and after WWII lead to the development of associated salts/esters and a search for new natural product antibiotics. This led initially to no new, marketable compounds, but concluded with the serendipitous discovery of fusidic acid, an antibiotic used to treat infections by Staphylococcus aureus, in 1960. The discovery process included contemporary approaches such as open innovation; targeting specific pathogens and/or specific organs in the patient; examining the effects of antimicrobial compounds on bacterial virulence as well as on antibiotic-resistant variants, and searching for antibiotic producers among microorganisms not previously well explored. These activities were promoted by the collaboration with a renowned Danish clinical microbiologist, K. A. Jensen, as well as company expertise in fermentation technologies, chemical synthesis and purification of bioactive compounds from organic materials.